PERBANDINGAN KRIM ANTIBAKTERI EKSTRAK PEGAGAN (Centella asiatica (L.) Urban) DENGAN VARIASI BASIS COLD CREAM DAN VANISHING CREAM TERHADAP Staphylococcus aureus - Sutrisno, Sahya Rania; Rahmawati, Ismi (Jurnal Farmasi & Sains Indonesia, 2025)
Cosmetic care products are designed to enhance human appearance. Centella asiatica (L). Urban, commonly known as gotu grain, is a natural ingredient that can be effectively used in anti-acne creams. The objective of this study is to investigate and compare the antimicrobial efficacy of cold cream and vanishing cream bases against Staphylococcus aureus, with a focus on determining their potential inhibitory effects. The preparation of cold cream involved a melt-emulsification process utilizing surfactants. In contrast, the vanishing cream was prepared using a melting method. Physical quality assessment was conducted through visual observation, evaluating organoleptic properties and homogeneity. The physical and antibacterial properties of the creams were evaluated using various standardized methods. Viscosity was measured using a Brookfield Viscometer, pH levels were assessed with a pH meter, spreadability and adhesion were evaluated using respective testers, and antibacterial activity was determined via the disc diffusion method. Statistical analysis of the physical quality test results was performed using the Independent Samples T-test, while antibacterial activity data were analyzed using One-Way ANOVA. The results of the physical quality evaluation revealed significant differences in the organoleptic properties among the gotu-gotu extract cream, cold cream base variation, and vanishing cream. However, no significant differences were observed in terms of homogeneity among the three formulations. The vanishing cream exhibited a significantly higher spreadability, with a mean value of 5.98 cm (n=3), compared to the cold cream base variation. Conversely, the vanishing cream displayed lower viscosity (mean: 3,560 cP, n=3) and adhesion (mean: 1.61 seconds, n=3) values compared to the cold cream base variation. The gotu-gotu extract cream formulated with a vanishing cream base exhibited potent antibacterial activity against Staphylococcus aureus, as evidenced by a significant inhibition zone diameter of 17.6 mm. This result meets the criteria for strong inhibition strength and is comparable to the positive control, demonstrating superior antibacterial efficacy relative to the cold cream base variation.